Altered mitochondrial metabolism in peripheral blood cells from patients with inborn errors of β‐oxidation. Issue 1 (26th August 2021) - Stenlid, Rasmus; Olsson, David; Cen, Jing; Manell, Hannes; Haglind, Charlotte; Chowdhury, Azazul Islam; Bergsten, Peter; Nordenström, Anna; Halldin, Maria
Abstract: Inborn errors of mitochondrial fatty acid oxidation (FAO), such as medium‐chain acyl‐CoA dehydrogenase deficiency (MCAD) and very long‐chain acyl‐CoA dehydrogenase deficiency (VLCAD) affects cellular function and whole‐body metabolism. Carnitine uptake deficiency (CUD) disturbs the transportation of fatty acids into the mitochondria, but when treated is a mild disease without significant effects on FAO. For improved clinical care of VLCAD in particular, estimation of FAO severity could be important. We have investigated whether the oxygen consumption rate (OCR) of peripheral blood mononuclear cells (PBMCs) obtained from patients with MCAD, VLCAD, and CUD can be used to study cellular metabolism in patients with FAO defects and to determine the severity of FAO impairment. PBMCs were isolated from patients with VLCAD ( n  = 9), MCAD ( n  = 5–7), and CUD ( n  = 5). OCR was measured within 6‐hours of venous puncture using the Seahorse XFe96. The PBMCs were exposed to glucose alone or with caprylic acid (C8:0) or palmitic acid (C16:0). OCR was significantly lower in cells from patients with β‐oxidation deficiencies (MCAD and VLCAD) compared to CUD at basal conditions. When exposed to C16:0, OCR in VLCAD cells was unchanged, whereas OCR in MCAD cells increased but not to the levels observed in CUD. However, C8:0 did not increase OCR, as would be expected, in VLCAD cells. There was no clear relationship between clinical severity level and OCR. In patients with β‐oxidation deficiencies, changes of mitochondrial respiration in PBMCs are detectable, which indicate that PBMCs have translational potential for studies of β‐oxidation defects. However, further studies are warranted.